Novinky v diagnostice a léčbě MEN1 - Starý, Karel (Vnitrni lekarstvi, 2015)
MEN1 syndrome is an autosomal dominant disorder caused by mutation in the men in gene located on the 11th chromosome. It is a rare disorder with incidence of 1 : 30 000. It involves functional or cancerous diseases of parathyroid glands, hypophysis, endocrine pancreas, adrenal glands, or other tumors. The diagnosis of MEN1 is suspected if at least 2 components of this multiple tumor syndrome occur simultaneously. The increase in diagnostic precision enables detection of MEN1 in its early stages. Currently, the most frequently discussed topics include the use of biomarkers for diagnostics and new approaches in surgical treatment of MEN1.
Keywords: Proto-Oncogene Proteins; protoonkogenní proteiny; Multiple Endocrine Neoplasia Type 1; mutace; Early Medical Intervention; časná lékařská intervence; Chromosomes, Human, Pair 11; Humans; mužské pohlaví; Male; lidé; Mutation; lidské chromozomy, pár 11; mnohočetná endokrinní neoplazie typu 1; Prognosis; prognóza